First Report of Sarcocystis Masoni in a Captive Alpaca (Vicugna Pacos) From China - Jiang, Nan; Xin, Shilin; Zhu, Niuping; Yang, Liulu; Huang, Wei; Hu, Junjie; Zhu, Xiuhong; Yang, Yurong (Frontiers in Veterinary Science, 2021)
Background: Sarcocystosis is a parasitic disease caused by intracellular protozoan parasite of the genus Sarcocystis. Tissue samples of alpacas (n=4) from Henan province (China) were screened for Sarcocystis spp. infection by histological examination, pepsin digestion and molecular assays. Results: Sarcocystis spp. was detected in heart, liver, spleen, lung, and kidney of an alpaca by molecular assays. Many sarcocysts with inflammation responses were observed in this alpaca myocardium, and they showed a high similarity to Sarcocystis masoni by sequence analysis. Conclusion: This study is the first to demonstrate Sarcocystis spp. infection in alpaca from China. The higher parasite load in the alpaca myocardium indicated that it had contacted with an environment contaminated with sporocysts, and that the alpaca was susceptible to Sarcocystis spp.